Alkyl Aryl Ether Bond Formation with PhenoFluor1. Issue 19 (20th March 2015) - Shen, Xiao; Neumann, Constanze N.; Kleinlein, Claudia; Goldberg, Nathaniel W.; Ritter, Tobias
Abstract An alkyl aryl ether bond formation reaction between phenols and primary and secondary alcohols with PhenoFluor has been developed. The reaction features a broad substrate scope and tolerates many functional groups, and substrates that are challenging for more conventional ether bond forming processes may be coupled. A preliminary mechanistic study indicates reactivity distinct from conventional ether bond formation.